2011
DOI: 10.1007/s00442-011-1933-0
|View full text |Cite
|
Sign up to set email alerts
|

Direct and socially-mediated effects of food availability late in life on life-history variation in a short-lived lizard

Abstract: Food availability is a major environmental factor that can influence life history within and across generations through direct effects on individual quality and indirect effects on the intensity of intra- and intercohort competition. Here, we investigated in yearling and adult common lizards (Zootoca vivipara) the immediate and delayed life-history effects of a prolonged food deprivation in the laboratory. We generated groups of fully fed or food-deprived yearlings and adults at the end of one breeding season.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In a previous study, we demonstrated that effects of food availability on life history were strongly influenced by age class, sex and asymmetric social interactions between birth cohorts (Mugabo et al . , ). Adult male common lizards are socially dominant over conspecifics and asymmetric competition for food between age and sex classes has been observed in the wild (Massot et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, we demonstrated that effects of food availability on life history were strongly influenced by age class, sex and asymmetric social interactions between birth cohorts (Mugabo et al . , ). Adult male common lizards are socially dominant over conspecifics and asymmetric competition for food between age and sex classes has been observed in the wild (Massot et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Mugabo et al . , ). Here, we found that negative density dependence was stronger in juveniles than in yearlings and adults and was stronger in females than in males, with adult males being little affected by density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, litter size may be influenced by female food consumption after hibernation (when vitellogenesis starts) and also by conditions experienced before vitellogenesis (e.g., Marquis et al, 2008). Common lizards are thought to use a mixed‐strategy in which they fuel reproduction with both stored and recently acquired resources (Avery, '75; Massot and Clobert, '95; Mugabo et al, 2011; Bleu et al, unpublished results). According to previous observations, litter size is a function of multiple mating (Fitze et al, 2005; Eizaguirre et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…) may be more important drivers of future body size than are influences post‐hatching (e.g., social environment, Mugabo et al. ; physiological performance, Clobert et al. ) for this species.…”
Section: Discussionmentioning
confidence: 95%